Artisan Entrepreneurship - Ratten, Vanessa; Jones, Paul 1967-; Braga, Vitor; Parra-López, Eduard (Emerald Publishing, 2022)
Artisan Entrepreneurshipanalyses handicraft enterprise using different approaches at an individual, group and societal point of view, providing a better understanding about how these workers contribute to societal wellbeing and aid cultural heritage preservation for future generations
Keywords: Kunsthandwerk; Dienstleistungssektor; Handwerk; Entrepreneurship; Kulturwirtschaft; ntrepreneurship; Handicraft industries; Entrepreneurship / Social aspects; Entrepreneuriat; Entreprises artisanales; Entrepreneuriat / Aspect social; entrepreneurs; Business & Economics / Entrepreneurship; Electronic books